Salvation in the Johannine Epistles - Van der Merwe, Dirk (HTS teologiese studies, 2004)
This article attempts to compile a soteriology in the Johannine Epistles. Circumstances and false teachings that might have influenced the theological doctrine and ethical behaviour of the community are constructed. The article argues that aspects which led to the reported schism, determine the structure and content of the soteriology. In the Johannine Epistles the “elder” teaches only basic aspects of soteriology. They are presented from theocentric and christocentric perspectives that are closely interwoven with different themes. The article demonstrates that soteriology is metaphorically presented from the perspective of the conduct of God the Father, reflecting a paternalistic Old Testament image of a household. The elder refers to three of God's characteristics: light (1:5), justice (2:29), and love (4:8). Believers have to direct their lives according to these characteristics once they have been born as children into the family of God and have experienced “eternal life.”